Penerimaan Honor/Upah Advokat dalam Perspektif Hukum Islam - Agustina Berutu; Aulia Fahira Hanan; Fauziah Lubis (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
In every job, honesty and great accountability are needed, especially in carrying out the mandate entrusted to workers, especially being an advocate. every problem from his client. In determining the honorarium for his client, he must pay attention to the condition of his client and in Islamic law there is no regulation regarding the halal or unlawful honorarium received by advocates in carrying out their work. his clients in the perspective of Islamic law and the purpose of this research is to find out the halalness of receiving honorariums in the perspective of Islamic law using the juridical-normative research method. The results of the study indicate that the honorarium paid ima by an advocate is lawful if the money received is not the result of fraud between the client and the advocate and justifies any means to win the client's case. Keywords: advocate, honorarium, halal